Claro Rafols Ceniza's rationalist theory of man: A critical synthesis of his epistemology, metaphysics, and ethics - Besa, Federico B., Jr. (Animo Repository, 2005)
This study demonstrates that Claro R. Ceniza has a rationalist theory of man. Ceniza himself did not present his theory as a philosophy of man. But through an analysis of his epistemology, metaphysics, and ethics, some important insights into mans nature become evident. Cenizas epistemology shows the extent of mans rational capacity; his metaphysics provides an explanation about mans place in nature, the unity of mind and body, the nature of the self, and the notion of freedom; and finally, his ethics unfolds the possibility for a good life. All these issues are made clear through a framework which makes use of basic anthropological questions such as what can man know?, what is the nature of reality?, what ought man to do?, and what may man hope? Rationalism is defined in the context of the seventeenth-century pre-Kantian modern philosophy. The theories of Descartes, Spinoza, and Leibniz serve as the basis for showing Cenizas rationalist theory of man. Two essential features of rationalism are given emphasis. The first is the belief in innate ideas or a priori truths. And the second is the application of deductive reasoning which begins with non-empirical principles or premises. In so far as the rationalists have applied this method in their theories about nature and man, such theories may also be regarded as rationalist. Cenizas postulates of thinking may be considered as a priori principles in the sense that man has the natural capacity for contracting them. The postulates are presuppositions of thought and they are logically prior to experience. Moreover, they are applicable not only to the actual world but also to possible worlds. Through the postulates of thinking, Ceniza derives and justifies his views about God, the world, and man. That Ceniza is a rationalist thinker is evident in his epistemological perspective. Therefore, in so far as his knowledge -claims about man are founded on his rationalist premises, such assertions belong to his rationalist theory of man. In this sense, Cenizas ideas about the unity of mind and body, freedom, moral life, and mans place in nature may constitute his rationalist philosophy of man.